Diabeł we frazeologii polskiej i rosyjskiej: motywy główne. - Iwczenko, Jarosława (Acta Polono-Ruthenica, 2009)
Basing on the phraseology and paremiology 3 groups of typical phraseological motives concer- ning devil are reviewed in the article. These are anthropomorphic devil, devil as a representative of chthonic word and Christian devil. The contamination of motives in each group is presented as well, also Russian and Polish devils images are compared.